2015
DOI: 10.1007/s12161-015-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantification Methods to Compensate for Matrix Effects in the Analysis of Benzalkonium Chloride and Didecyldimethylammonium Chloride in Fruits and Vegetables by LC-ESI-MS/MS

Abstract: Given the extensive presence of some toxic quaternary ammonium compound residues in foodstuffs arriving into the EU during 2012, the Food Authority Control of Geneva decided to implement a monitoring plan to investigate the presence of these contaminants in food: a method based on quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction and liquid chromatography electrospray tandem mass spectrometry was developed for analyzing didecyldimethylammonium chloride and four benzalkonium chloride homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To assess the activity of QACs on Enterococcus growth or survival under diverse environmental conditions that mimic real contexts, MIC BC and MBC BC were determined in anaerobic conditions (e.g., occurring in sewage) ( 37 , 38 ), room temperature (22°C; representing abiotic surfaces in healthcare or agri-food sectors) ( 39 ), and mildly acidic pH (pH = 5; resembling human skin and fresh fruits/vegetables contaminated with QACs residues) ( 40 42 ). BC was the QAC chosen for the susceptibility assays with modified conditions, as both species demonstrated higher tolerance and phenotype variability (wider MIC and MBC ranges) to this compound compared to DDAC under standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the activity of QACs on Enterococcus growth or survival under diverse environmental conditions that mimic real contexts, MIC BC and MBC BC were determined in anaerobic conditions (e.g., occurring in sewage) ( 37 , 38 ), room temperature (22°C; representing abiotic surfaces in healthcare or agri-food sectors) ( 39 ), and mildly acidic pH (pH = 5; resembling human skin and fresh fruits/vegetables contaminated with QACs residues) ( 40 42 ). BC was the QAC chosen for the susceptibility assays with modified conditions, as both species demonstrated higher tolerance and phenotype variability (wider MIC and MBC ranges) to this compound compared to DDAC under standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in Section 2.4, FDA suggests performing a parallelism between SAM and surrogate matrix or analyte to justify their use, but they do not provide any information about the number of calibrants required for SAM. Considering the literature, most authors use between four and six spiked concentrations [96,[129][130][131]. As with the EC approach, the use of IS to correct for procedural errors is recommended when a sample preparation that is different from simple "dilute and shoot" is performed [130].…”
Section: Isc With Authentic Analyte(s): Standard Addition Methods (Sam)mentioning
confidence: 99%
“…SAM can also be applied when the calibration curve is polynomial, particularly when high endogenous signals affect the linearity of the response due to detector saturation. For example, Díez et al showed that linear fitting provides adequate recoveries for antibiotic quantification in fruits and vegetables when concave SAM curves are obtained, while quadratic extrapolation could be used for convex or slightly concave curves [131].…”
Section: Isc With Authentic Analyte(s): Standard Addition Methods (Sam)mentioning
confidence: 99%
“…Hrubec [ 20 ] detected QACs in 80% of the subjects studied, indicating a clear relationship between QACs in blood and health-related biomarkers. Asthmatic reactions induced by BAC and DADMAC in QACs have been confirmed in a few cases via bronchial provocation tests [ 21 ]. A French physician-based notification program for work-related asthma [ 19 ] reported a marked increase in incident cases due to QACs, rising from 1.4% in 2001of reported cases in 2009 to 8.3%, mainly in the health and social sectors.…”
Section: Introductionmentioning
confidence: 99%